Cyorgenic Bacteria - Cassell, Albert F. (My University, 1905)
Introduction: In the early history of bacteria, Ostrn Passet and others made demonstrations showing the micrococci were present in pus of acute abscesses. This inference led some scientists to believe, that there can be no pus formation without the presence of these microorganisms. But this gave an erroneous idea of the study of bacteria. It has been shown by scientists that certain chemicals introduced beneath the skin give rise to pus formation independently of bacteria. Among the several chemicals tested which give positive results are Nitrate of silver, oil of turpentine, Strong liquid ammonia and a number of others. It has been shown that when pus cocci have been sterilized by heat, and then injected subcutaneously will still give rise to formation. Pasteur was the first investigator. In 1878 he secured results from sterilized tubes of pus as well as from the living organisms.
Pus Organisms
Citation: Cassell, Albert F. Cyorgenic Bacteria. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Microorganisms; Surgery; Staphylococcus; Theses; Manuscripts (documents)